Review of Cesarean Section on Maternal Request in a Tertiary Care Institute; Scenario in Developing Country - Panda, S; Jha, V; Singh, AS (Kathmandu University Medical Journal, 2015)
Mother requesting of caesarean reflects a belief among society that elective caesarean safer than vaginal delivery in term of fetus and mother. Although the study data neglecting the facts other skewed part in this issue is consideration of resources, as in developing countries, where maternal mortality is still high due to lack of adequate resources. Mother coming to obstetrician with mother’s request should individualize in every case considering mother’s argument, society and evidence base guideline. Kathmandu Univ Med J 2013; 11(4): 349-354